2014
DOI: 10.1371/journal.pntd.0002653
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review and Prevalence Analysis of Soil-Transmitted Helminth Infections in Honduras

Abstract: BackgroundHonduras is endemic for soil-transmitted helminth (STH) infections, but critical information gaps still remain on the prevalence and intensity of these infections as well as on their spatial distribution at subnational levels.ObjectivesFirstly, to review the research activity on STH infections in Honduras and secondly, to carry out a national prevalence analysis and map the geographical distribution of these infections in children.MethodsA systematic search was conducted of the published and grey lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 34 publications
3
21
0
Order By: Relevance
“…School teachers reported that the school is reached by the national deworming program and thus receives a single-dose 400 mg albendazole tablet per child on a yearly basis. No records are kept at the school in terms of deworming tablets intake and no parasitological baseline data have been obtained during governmental surveys (data reviewed in [27]). To our knowledge, prior to the present study, two parasitological surveys had been undertaken in the study community.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…School teachers reported that the school is reached by the national deworming program and thus receives a single-dose 400 mg albendazole tablet per child on a yearly basis. No records are kept at the school in terms of deworming tablets intake and no parasitological baseline data have been obtained during governmental surveys (data reviewed in [27]). To our knowledge, prior to the present study, two parasitological surveys had been undertaken in the study community.…”
Section: Discussionmentioning
confidence: 99%
“…The concerning association between trichuriasis and chronic malnutrition, along with the fact that T. trichiura has been found consistently as the most prevalent geohelminth in Honduras [27, 35, 36], suggests that (i) a reexamination of the current deworming guidelines are necessary; (ii) improvements in sanitary conditions and health education are indispensable components of STH control initiatives; and (iii) it is important to monitor for potential benzimidazole resistance in this parasite [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the frequency of deworming in the schools showed only a marginally significant effect in T. trichiura prevalence, which is likely due to the low efficacy of single-dose albendazole/mebendazole against this parasite [66, 67, 85]. This might explain why this and other Honduran studies show that T. trichiura is becoming the predominant STH species in the country [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Since 2001, the Honduran government has systematically tackled the challenge of decreasing the burden of these infections [10, 20]. Preventive chemotherapy through national deworming campaigns targeting school-age children (and more recently pre-school children) implemented by the Ministries of Health and Education with the technical support of PAHO/WHO has been the chief intervention, as is the case in all endemic countries [4].…”
Section: Introductionmentioning
confidence: 99%
“…Increased prevalence was associated with lower Human Development Index (HDI). 12 Other studies describing the prevalence, health impact, and risk factors of STH infections in Honduran schoolchildren have recently been undertaken in the rural populations 7,13 and across the country's ecological regions.…”
Section: Introductionmentioning
confidence: 99%